Implementation of the Focus Group Discussion (FGD) Method to Understand the Book Dalīl ʿAmal fī iʿdād al-Mawādd by Rusdy Ahmad Thu'aimah - Al Haqiqy, Muhammad Syihabul Ihsan; Agustina, Rahmah Fadhilah; Hadawiyah, Rabiatul (STIQ Amuntai, 2025)
Understanding Arabic academic texts often poses a challenge for students, particularly when the material contains complex structures. This study contributes novelty by applying the Focus Group Discussion method in teaching maharah qirāʾah through the study of Dalīl ʿAmal fī Iʿdād al-Mawādd by Rusdy Ahmad Thuʾaimah in an Islamic higher education context. The research aims to describe the implementation of FGD in understanding the book Dalīl ʿAmal fī Iʿdād al-Mawādd by Rusdy Ahmad Thuʾaimah. The subjects of this study were lecturers and postgraduate students of Arabic Language Education at UIN Maulana Malik Ibrahim Malang during the 2023/2024 academic year. Data were collected through participatory observation over one semester, interviews with ten students, and documentation related to the textbook and instructional design. Data analysis employed the Miles, Huberman, and Saldana model. The results of this study reveal that the implementation of FGD in understanding Dalīl ʿAmal fī Iʿdād al-Mawādd was carried out in three stages: first, preparation, including group division and role assignment; second, implementation, consisting of presentations, discussions, question and answer; and third, conclusion, involving a summary of results and lecturer feedback. This process encouraged students not only to engage in individual reading but also to exchange understandings and construct meaning collectively. Supporting factors included the relevance of participants’ backgrounds, the systematic structure of the book, and the role of the facilitator, while inhibiting factors comprised differences in Arabic proficiency levels, time constraints, and limited participant preparation.